Synthesis of 4-chalcogenyl pyrazoles via electrophilic chalcogenation/cyclization of α, β-alkynic hydrazones. Issue 9 (25th February 2020) - Yu, Xinzhang; Shang, Yu-Zhu; Cheng, Yu-Fei; Tian, Jun; Niu, Yulan; Gao, Wen-Chao
Abstract : 4-Chalcogenyl pyrazoles, including the 4-sulfenyl celecixib derivative, are accessed through cyclization of α, β-alkynic hydrazones induced by S-electrophiles prepared in advance or generated in situ . Abstract : A facile method for the synthesis of 4-chalcogenylated pyrazoles has been developed via electrophilic chalcogenation/cyclization of α, β-alkynic hydrazones. The cyclization of α, β-alkynic aldehyde hydrazones could be induced by using either sulfenyl chloride or the S-electrophiles generated in situ from the reaction of NCS and arythiol. The developed method was successfully applied to the synthesis of the sulfenyl analogue of celecoxib.